Low dose Galcanezumab for treating trigeminal autonomic cephalalgias: clinical observation from Colombia and Mexico on behalf of ASOLAC - Muñoz-Cerón, Joe; Rodríguez, Ildefonso; Guerra, Carolina; Vélez, Karina; Hernández, Natalia; Nieto-Rodríguez, Paula; Barrera, Daniela Gomez (Headache Medicine, 2025)
Background Although evidence exists regarding the efficacy of galcanezumab in treating cluster headaches and other trigeminal autonomic cephalalgias (TACs), data on its effectiveness at lower doses are still lacking. Objective To report the clinical outcomes of Latin American patients treated with galcanezumab (GNZ) at a dose approved for migraine. Methods This case series included patients with cluster headaches, hemicrania continua, and short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT-SUNA) who were treated with a 240 mg loading dose of GNZ followed by 120 mg monthly. Results A total of 18 subjects were included: 12 with cluster headaches, 4 with hemicrania continua, and 2 with SUNCT-SUNA who received 1 to 24 monthly cycles of GNZ. Among those with episodic cluster headaches, 7 of 8 patients experienced a reduction in attack frequency of more than 50%. In the chronic cluster headache group, this reduction was achieved in 2 of 4 patients. Additionally, 2 of the 4 patients with hemicrania continua became headache-free. In the SUNCT-SUNA group, 2 were included, both reduced their daily attack frequency from 120 to 30 and from 10 to 2, respectively. Conclusions These clinical observations suggest that lower doses of GNZ may be a viable option for treating Latin American patients with TACs.